2019
DOI: 10.1108/pr-07-2017-0217
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice and knowledge sharing behavior

Abstract: Purpose Knowledge sharing (KS) has been consistently acknowledged as a critical factor in the organizational development and the betterment of employees. The purpose of this paper is to extend previous empirical research on KS by testing psychological ownership as an underlying mechanism between the relationship of organizational justice (OJ) and KS behavior in developing country context. The authors also examine the moderating role of perceived organizational support (POS) between psychological ownership and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 136 publications
(190 reference statements)
4
43
1
1
Order By: Relevance
“…In this context, organizational justice plays a critical role. In line with recent available empirical evidence [14,111,112], our results indicate the importance of organizational justice as a direct antecedent of KS. In addition, perceived organizational support and affective organizational commitment also exert direct effects on KS.…”
Section: Overview Of Key Findingssupporting
confidence: 91%
“…In this context, organizational justice plays a critical role. In line with recent available empirical evidence [14,111,112], our results indicate the importance of organizational justice as a direct antecedent of KS. In addition, perceived organizational support and affective organizational commitment also exert direct effects on KS.…”
Section: Overview Of Key Findingssupporting
confidence: 91%
“…Teaching experience, rank, and levels of education are not predictors for the knowledge externalization and combination processes, while the collaborative culture does predict the externalization process only. These findings are same as those in the studies of Zhao (2010) and Hameed et al (2019), which reflect that institutionalizing of the SECI mechanism depends on a collaborative culture rather than teacher individual factors. In the Hong Kong school context, almost all the teachers are bachelor's degree holders with teacher-training qualifications.…”
Section: Discussionsupporting
confidence: 89%
“…To isolate the cultural effect of schools from characteristics of individual teachers, the data structure of this study will be a two-level model with residuals at the teacher level and school level (Hox et al, 2018;Rabe-Hesketh et al, 2009). Although education level, years of experience, and working experience (age) have been found to be uncorrelated with the behaviours for knowledge sharing (Hameed et al, 2019;Zhao, 2010) in multivariate designs, it is still worth testing these factors to identify the existence of the influences from both teacher individual-level and school-level hierarchies on knowledge sharing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the psychological ownership concept is a significant predictor of attitudes, behaviors, and motives at the individual-level in a workplace [28,29]. Avey, Avolio, Crossley, and Luthans [62] investigated psychological ownership and found a positive impact on citizenship behavior, job satisfaction, and commitment, while a negative relation is found with the deviant behavior of employees.…”
Section: Moderating Role Of Psychological Ownershipmentioning
confidence: 99%
“…We argue that employees who felt abused by their supervisors will feel unobligated to benefit their organizations and will hide knowledge, which may decrease organizational effectiveness. Furthermore, prior studies have shown that psychological ownership is an important predictor of individuals' attitudes and behaviors [28,29]. Hence, it can be used as a significant factor for attenuating the relationship between abusive supervision and KH.…”
Section: Introductionmentioning
confidence: 99%